2006
DOI: 10.1038/sj.cdd.4401837
|View full text |Cite
|
Sign up to set email alerts
|

Roles for NF-κB in nerve cell survival, plasticity, and disease

Abstract: Here we review evidence of roles for NF-jB in the regulation of developmental and synaptic plasticity, and cell survival in physiological and pathological settings. Signaling pathways modulating NF-jB activity include those engaged by neurotrophic factors, neurotransmitters, electrical activity, cytokines, and oxidative stress. Emerging findings support a pivotal role for NF-jB as a mediator of transcription-dependent enduring changes in the structure and function of neuronal circuits. Distinct subunits of NF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
382
0
13

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 519 publications
(416 citation statements)
references
References 100 publications
13
382
0
13
Order By: Relevance
“…Of the secreted neurohumoral substances, PDGF, IGF, TGF-β1 and IL-10 have critical roles in preventing neural apoptosis via the PI3K-Akt/NF-κB pathway [20][21][22]37 . Nerve growth factor and BDNF prevent activation of the mitochondrial apoptotic pathway via the P75NTR-mediated NF-κB pathway 23,38 . NF-κB activation induces the upregulation of anti-apoptotic genes, including Bcl-2 and Bcl-xL 20,23, and the Akt pathway could independently block the mitochondrial apoptotic pathway 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Of the secreted neurohumoral substances, PDGF, IGF, TGF-β1 and IL-10 have critical roles in preventing neural apoptosis via the PI3K-Akt/NF-κB pathway [20][21][22]37 . Nerve growth factor and BDNF prevent activation of the mitochondrial apoptotic pathway via the P75NTR-mediated NF-κB pathway 23,38 . NF-κB activation induces the upregulation of anti-apoptotic genes, including Bcl-2 and Bcl-xL 20,23, and the Akt pathway could independently block the mitochondrial apoptotic pathway 23 .…”
Section: Discussionmentioning
confidence: 99%
“…159 The reasons for these discrepancies are not clear, but may stem from the fact that NF-B has prosurvival effects in neurons and other cell types. 160 Nevertheless, microglial NF-B activation in brain ischemia appears to be largely neurotoxic.…”
Section: Nf-b and Ap-1mentioning
confidence: 99%
“…Nuclear factor kappa B (NFκB) is another non-histone substrate for acetylation; its function in synaptic plasticity and several types of LTM has previously been established and reviewed elsewhere [192,193]. Interestingly, in cultured cells, it was shown that CBP and p300 acetylate the NFκB p65 subunit in a stimulus-dependent manner, which, subsequently, could be deacetylated through HDAC3.…”
Section: Non-histone Protein Acetylation In Synaptic Plasticity and Mmentioning
confidence: 99%